On international equity weights and national decision making on climate change - David Anthoff; Richard S. J. Tol (Center for Economic Studies and ifo Institute (CESifo), 2008)
Estimates of the marginal damage costs of carbon dioxide emissions require the aggregation of monetised impacts of climate change over people with different incomes and in different jurisdictions. Implicitly or explicitly, such estimates assume a social welfare function and hence a particular attitude towards equity and justice. We show that previous approaches to equity weighing are inappropriate from a national decision maker's point of view, because domestic impacts are not valued at domestic values. We propose four alternatives (sovereignty, altruism, good neighbour, and compensation) with different views on concern for and liability towards foreigners. The four alternatives imply radically estimates of the social cost of carbon and hence the optimal intensity of climate policy.
Keywords: Q54; 330; Domestic climate policy; social cost of carbon; equity weights; Klimaschutz; Luftverunreinigung; Soziale Kosten; Gerechtigkeit; Theorie; Welt